The Relationship between Self-Efficacy, Digital Literacy and Students’ English Achievement in Grade Eight at SMP Islam Al Azhar 37 Pekanbaru - Armayanti, Dona; Zulhidah, Zulhidah; Settiawan, Dodi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study is a correlational quantitative research that aims to determine the Relationship between Self Efficacy and Digital Literacy on English Learning Achievement of Grade VIII Students of Al Azhar Islamic Junior High School 37 Pekanbaru. The formulation of the problem in this study is "Is there a Relationship between Self Efficacy and Digital Literacy on the English Learning Achievement of Grade VIII Students of Al Azhar Islamic Junior High School 37 Pekanbaru?". The population of this study is all students at Al Azhar Islamic Junior High School 37 Pekanbaru, with a sample of grade VIII students. The instruments used to collect data in this study consisted of questionnaires and documentation. From the analysis of the data obtained, it can be concluded that there is a relationship between Self Efficacy and Digital Literacy on the English Learning Achievement of Grade VIII Students of Al Azhar Islamic Junior High School 37 Pekanbaru. This is evidenced by the value of F calculated (56,513) > F table (3,119) or a significant level (0.000) < 0.058 so that H0 is rejected and Ha is accepted, which means that there is a relationship between Self Efficacy and Digital Literacy on the English Learning Achievement of Grade VIII Students of Al Azhar Islamic Junior High School 37 Pekanbaru.